The mediating role of money desire in death anxiety toward materialism among young adults in Malaysia - Bong, Britney Sue Fun; Choong, Jemimah Giet Hee; Kwok, Koh Yee (2022)
Society has been embracing materialism culture even in the midst of economic recession. Nevertheless, materialism would elicit innumerable detrimental outcomes and be profoundly influenced by underlying psychological conditions. Therefore, the objective of the research is to explore the mediating role of money desire in death anxiety toward materialism among young adults in Malaysia. A quantitative research specifically cross-sectional study and quota sampling procedure was incorporated to recruit 129 participants across Malaysia. The questionnaires included the Death Anxiety Inventory-Revised (DAI), Heintzelman Greed Scale (HGS), and Material Value Scale (MVS). Data was collected through self-administered online questionnaires and was distributed via social media networks (i.e., WhatsApp, Facebook and Instagram). The recruited respondents are young adults aged 18 to 25 years old. The present study managed to recruit nearly equal numbers of gender which were 66 females and 63 males. The participants are also ethnically diverse which are 30.2% Chinese, 37.2% Malay, 27.1% Indian, and 5.4% others. The results showed that death anxiety positively predicts money desire, money desire positively predicts materialism, death anxiety positively predicts materialism. Money desire have partial mediating effects on death anxiety to materialism. Consequently, the findings contributed implication to the research field as previous literature has been outdated and it shed a light on the adoption of theories (i.e., terror management theory and self-determination theory). Moreover, the finding contributes to the society, future researchers, and policymakers to conduct appropriate intervention and spread awareness.